Pemidanaan dan Pertimbangan Hakim terhadap Pelaku Tindak Pidana Pencurian dengan Pemberatan - Ry Bunga Dwi Pertiwi; Hadri Abunawar (Faculty of Law Universitas Muhammadiyah Metro, 2025)
Indonesia is a state of law, not a state of power, so legal status must be above all. In people's lives, there are always behaviors which possibly break the law, for example, theft by weighting. Cases of weighted thefts still dominates criminal acts that occurred in East Lampung regency with a total of 193 cases in 2020 and continue to increase to date. Economic problems are the main causes of weighted thefts. This research was an empirical juridical legal research, in which the procedures used were aimed at solving research problems. The research secondary data will first be utilized then conducting the next stage on getting the research primary data in the field. The empirical juridical method approach in this study, were guided by laws and regulations and also the results of data collection and interviews through field studies. The results of this study gained that: 1. The provisions for the crime of theft by weighting according to a positive law perspective, in Article 363 of the Criminal Code (Book of Criminal Law) with a maximum penalty of seven years in prison and punishable by imprisonment for a maximum of 9 (nine years) if the theft fulfills point (3) accompanied by one of the things in point (4) and (5) of Article 363 of the Criminal Code. 2. The judge has various considerations in making a decision on the perpetrators of the crime of theft by weighting. Namely: suitability of the perpetrator's identity, the elements charged by the public prosecutor have been fulfilled, and considering aggravating and mitigating circumstances.